Pelaksanaan Pendaftaran Tanah Sistematis Lengkap di Desa Menanga, Kecamatan Rendang, Kabupaten Karangasem - Nyoman Handytya Wiarsa Putra; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2021)
Complete systematic land registration is a program organized by the government, specifically the